2018
DOI: 10.1177/000313481808401001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Children's Hospital Designation on Outcomes and Costs after Cholecystectomy in Adolescent Patients

Abstract: Variations in the management of adolescents at children's hospitals (CHs) and nonchildren's hospitals (NCHs) have been well described in the trauma literature. However, the effects of CH designation on outcomes after common general surgical procedures have not been investigated. The purpose of this study was to compare the outcomes and costs of adolescent cholecystectomies performed at CHs and NCHs. Within the California State Inpatient Database (2005–2011), we identified 8117 cholecystectomy patients aged 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Many previous studies have shown higher charges or costs at CHs versus NCHs for all pediatric inpatients, 28 pediatric asthma, 29,30 severe pediatric sepsis, 31 and common surgical procedures. [32][33][34][35][36][37] Some show equivalent outcomes regardless of hospital type, such as for malrotation surgery 38 and neonatal herpes simplex. 7 Others show poorer outcomes at non-CHs, such as increased LOS and complications with pyloromyotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have shown higher charges or costs at CHs versus NCHs for all pediatric inpatients, 28 pediatric asthma, 29,30 severe pediatric sepsis, 31 and common surgical procedures. [32][33][34][35][36][37] Some show equivalent outcomes regardless of hospital type, such as for malrotation surgery 38 and neonatal herpes simplex. 7 Others show poorer outcomes at non-CHs, such as increased LOS and complications with pyloromyotomy.…”
Section: Discussionmentioning
confidence: 99%